Irritable Bowel Syndrome on Inflammatory Bowel Disease in Deep Remission: No Relation with Remission Deepening and Inflammation - Sezgin, Orhan; Boztepe, Burcu; Üçbilek, Enver; Altintas, Engin; Celikcan, Havva Didem (Turkish Journal of Gastroenterology, 2021)
Background: The aim of the study was to establish the frequency of irritable bowel syndrome (IBS) in patients with inflammatory bowel disease (IBD) in clinical, endoscopic, and histologic remission and in relation to both the depth of remission and inflammation markers. Methods: Patients with ulcerative colitis (UC) and with Crohn’s disease (CD) in clinical remission for at least 6 months were enrolled in the study. All of the patients underwent colonoscopy, and biopsy specimens were taken to evaluate endoscopic and histopathologic remission. Patients were evaluated according to Rome III criteria for IBS. Fecal calprotectin level and blood samples for C-reactive protein (CRP), sedimentation rate, and fibrinogen levels were studied. Results: IBS frequency was 20.9% in UC cases and 28.9% in CD cases in clinical remission. Rates with and without endoscopic remission in UC (20.5% vs. 22.2%, P = .727) and CD (25% vs. 33.3%, P = .837, respectively) were not different. Similarly, rates with and without histopathologic remission in UC (15.7% vs. 26.6%, P = .723), and CD (21.4% vs. 33.3%, P = .999) were not statistically different. Also, it was not related to inflammation markers. Conclusion: IBS frequency among IBD patients with remission was in a substantial rate; these rates kept up with the process of deep remission and even complete mucosal healing and were irrelevant to inflammation.